Benefits of Information Technology in Education - Dona Santika; Aisyah Amini Saragih; Muthi Nur Hanifah (Integrasi: Jurnal Studi Islam dan Humaniora, 2023)
The purpose of this study was to determine the effect of information technology on education. This research is a literature study which is a type of qualitative research. The data analysis used is the Miles and Huberman analysis model, namely collecting data, reducing data, presenting data and drawing conclusions. The results of this study are that information technology is man-made to help make it easier for humans to find and receive information, especially in the world of education. The benefits that can be felt with the existence of information technology are as follows: (1) To facilitate activities in school management; (2) As a medium of information in learning; (3) Assist and support development. The purpose of this research is to determine the effect of information technology on education. This research is a literature study which is a type of qualitative research. The data analysis used is the Miles and Huberman analysis model, namely collecting data, reducing data, presenting data and drawing conclusions. The results of this study are that information technology is man-made to help make it easier for humans to find and receive information, especially in the world of education. The benefits that can be felt with the existence of information technology are as follows: (1) To facilitate activities in school management; (2) As a medium of information in learning; (3) Assist and support educational development.